Antigen-G of Larva Serum of Musca domestica as an Immunoglobulin Production Promoter in Goats under an Organic Maintenance - Rumokoy, Laurentius; Kiroh, Hengky; Untu, Ivonne Maria; Assa, Geertruida; Turangan, Santie; Toar, Wisje Lusia (ANIMAL PRODUCTION, 2020)
This experiment aimed to reveal the effect of serum G-antigen of M. domesticainsect larvae (LAS) as promoter antigen on serum immunoglobulin production in organically managed goat livestock. This study used 12 local goats which were divided into two groups: as a control group and treated group receiving treatment. Insect rearing was conducted to obtain the larvae, the antigen-G was then extracted from the larvae to be used as promoter antigen to enhance the serum antibody production which was subcutaneously immunized in experimental goats and incubated for a period of 14 days. Blood collection of 2.5 ml was taken through the jugular vein and then carried out a quantification of serum protein level indicating the antibody proportion of goats. The data of the LSA extract proportion level were statistically analyzed with t-test, and the quality classification level of serum immunoglobulin of animal groups were statistically analysed. The results showed that the serum of animal treated with LSA of M. domesticaresulted in a higher level of immunoglobulin (P <0.01) compared to the control. We conclude that the antigen-g substance (LSA) could support the efforts to improve the production of organic goat livestock by increasing the total level of antibodies circulating in the blood.